2014
DOI: 10.1016/j.jmpt.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Ventral and Dorsal Neck Muscle Layers During Loading Against Gravity in Healthy Volunteers Using Speckle Tracking

Abstract: Running head -no more than 40 letters/ spacesNeck muscles mechanical activation during a head lift Word count for structured abstract (approx 250 words or less) 185Word count for text (excludes abstract, figure legends, references) 2999 Practical ApplicationsThree to 5 short sentences that highlight findings of the study. These statements should relate directly to the study findings.The present results show the need for deep neck muscles to act as neck stabilizers to resist gravity.During this highly demanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…1,9,19 Although earlier studies focused on tracking the cardiac organs or blood flow, speckle tracking studies have become widely used to estimate the displacement and strain of tendons or muscles. 12,13,20,22 Stegman et al demonstrated the efficacy and accuracy of 2D STE in estimating the displacement of the flexor digitorum superficialis (FDS) tendon. 22 They assessed the displacement of the FDS tendon using 2D STE at wrist level while a video microscope simultaneously imaged the exposed FDS tendon as a reference for validation during open carpal tunnel surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,19 Although earlier studies focused on tracking the cardiac organs or blood flow, speckle tracking studies have become widely used to estimate the displacement and strain of tendons or muscles. 12,13,20,22 Stegman et al demonstrated the efficacy and accuracy of 2D STE in estimating the displacement of the flexor digitorum superficialis (FDS) tendon. 22 They assessed the displacement of the FDS tendon using 2D STE at wrist level while a video microscope simultaneously imaged the exposed FDS tendon as a reference for validation during open carpal tunnel surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscles actively contract and produce force in response to control signals from the central nervous system, leading to mechanical changes in the muscles. Ultrasound enables quantitative descriptions of these mechanical changes and allows non-invasive investigation of different muscle layers in real time and in vivo 19 20 21 22 . Ultrasound with post-process speckle tracking analysis 23 measures deformation (mechanical muscle changes, such as elongations and shortenings of the muscle) and deformation rate (how fast the deformation occurs) simultaneously in the superficial and deep neck muscle layers.…”
mentioning
confidence: 99%
“…The study findings support our hypothesis that cervical muscle deformation versus time curves is a better method for evaluating ultrasound speckle tracking analysis than calculating the average RMS 17 . Our recent study 17 analyzing ultrasound speckle tracking using average RMS values of deformation curves 19,20 showed a weak relationship between RMS and force (R 2 = 0.03–0.18). In contrast, the present study showed that 16 of 20 individuals demonstrated a subject-specific strong to very strong linear relationship (9 individuals) or non-linear relationship (7 individuals) between the percentage of MVC and muscle deformation when the five neck muscles were summed together.…”
Section: Discussionmentioning
confidence: 96%